2010
DOI: 10.1016/j.foodres.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium headspace analysis of volatile flavor compounds extracted from soursop (Annona muricata) using solid-phase microextraction

Abstract: a b s t r a c tThe influence of headspace solid-phase microextraction (HS-SPME) variables, namely, sample concentration, salt concentration and sample amount, on the equilibrium headspace analysis of the main volatile flavor compounds released from soursop was investigated. A total of 35 volatile compounds, comprising 19 esters, six alcohols, three terpenes, two acids, two aromatics, two ketones and an aldehyde, were identified. The results indicated that all response-surface models were significantly (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…Similar observations were also reported in previous studies (Mirhosseini et al, 2007;Cheong et al, 2010;Cheong et al, 2011), where extraction efficiency increased with addition of salt. Mirhosseini et al (2007) observed that average total peak areas improved by 47 % to PDF Creator -PDF4Free v2.0 http://www.pdf4free.com effect salt on the extraction efficiency of volatiles from a matrix from a purely technical point of view, with a goal for extracting volatiles qualitatively, hence, much higher levels of salt were investigated (0-30 % w/v).…”
Section: Validation Of Optimal Conditionssupporting
confidence: 92%
“…Similar observations were also reported in previous studies (Mirhosseini et al, 2007;Cheong et al, 2010;Cheong et al, 2011), where extraction efficiency increased with addition of salt. Mirhosseini et al (2007) observed that average total peak areas improved by 47 % to PDF Creator -PDF4Free v2.0 http://www.pdf4free.com effect salt on the extraction efficiency of volatiles from a matrix from a purely technical point of view, with a goal for extracting volatiles qualitatively, hence, much higher levels of salt were investigated (0-30 % w/v).…”
Section: Validation Of Optimal Conditionssupporting
confidence: 92%
“…According to Cheong et al (2010), A. muricata fruit have many volatile flavor compounds. Thus, research on the quantitative descriptive analysis and intentions to purchase/ consumption are necessary to map the best sensory profile of the products studied, since volatile flavor compounds in A. crassiflora pulp could influence the acceptance thereof.…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl esters were formed through enzymatic and chemical esterification of fatty acids interacting with ethanol during fermentation and the long-term aging process. [37][38][39] Among ethyl esters, the major compounds determined were ethyl acetate, ethyl-2-hydroxypropanoate, ethyl octanoate, ethyl benzoate, diethyl succinate, ethyl tetradecanoate, ethyl hexadecanoate, (Z)-9-octadecenoic acid ethyl ester, and linoleic acid ethyl ester in HQW and WQW. Among the alcohols, 2-phenylethanol, 2-methyl-1-propanol, and 3-methyl-1-butanol exhibited relatively higher contents, which accounted for 90.46% of the total quantity of alcohols during brewing.…”
Section: Identification and Determination Of Volatile Flavour Compounmentioning
confidence: 99%